To Assess the Quality of Life in Patients Suffering from Allergic Rhinitis - Nikhil Sharma; Prithpal S. Matreja; Monika Gupta; Vipan Gupta; Manish Gupta; Ashwani K. Gupta (Journal of Basic & Applied Sciences, 2015)
Background: Allergic Rhinitis (AR) associated with impairments in patients day-to-day functioning at home and work is a global health problem. It’s associated with sleep disorders, emotional problems, impairment in activities, and social functioning. However, it’s not known to what extent quality of life (QOL) scores, work impairment, or sleep is altered in Indian setup hence, this study was designed to assess the quality of life of patients suffering from allergic rhinitis. Methodology: This prospective, observational, cross sectional study was conducted on patients suffering from allergic rhinitis visiting the out patients | department. The patients who gave written informed consent were divided into two groups based on gender, Group 1 was males and Group 2 was females. A detailed history was taken and participants underwent thorough medical examination, followed by assessment on Rhino conjunctivitis Quality of Life Questionnaire (RQLQ) and WHOQOL – Bref scores. Results: A total of 87 patients were screened of which 40 patients were enrolled in study. The average age of patients in the study was 28.08±10.01, a total of 26 males and 14 females completed the study. There were significantly worse non nose/eyes symptoms scores, practical problems, and emotional scores in patients in Group 2 as compared to Group 1. Group 1 had better aspect of sleep, nasal symptoms, and eyes symptoms as compared to Group 2. Whereas, Group2 had better aspect of activities score as compared to Group 1. Conclusion: To conclude both groups had compromised quality of life, with females being more affected as compared to males